Facile solution combustion synthesis of MoO2 nanoparticles as efficient photocatalysts. Issue 43 (25th October 2017) - Gu, Siyong; Qin, Mingli; Zhang, Houan; Ma, Jidong; Wu, Haoyang; Qu, Xuanhui
Abstract : Efficient foam-like MoO2 photocatalysts assembled from 20–30 nm nanoparticles were one-step fabricated by a solution combustion synthesis method. Abstract : Foam-like MoO2 assembled from nanoparticles was fabricated by a solution combustion synthesis method using hexaammonium molybdate, ammonium nitrate (NH4 NO3 ) and glycine as the precursors. The effect of the glycine/NH4 NO3 ratio ( Φ = 0.25, 0.50, 0.75, 1.0 and 1.25) on the physicochemical properties of the final products was systematically studied. The Φ value was found to display significant roles in the final phases and morphologies of the products. With a Φ value of 0.50, the foam-like product consisting of MoO2 nanoparticles with an average size of about 20–30 nm was synthesized. The photocatalytic activities of the foam-like MoO2 towards degradation of several contaminants, including methyl orange (MO), methylene blue (MB), rhodamine B (Rh B) and phenol, were investigated. The foam-like MoO2 offered excellent capability and stability toward photocatalytic degradation of the studied contaminants. The results reported here demonstrated that rational design of MoO2 -based photocatalysts might be able to improve their properties in energy conversion and environmental preservation.